Surface treatment method of metal composite

By coarsing the first metal portion of the irregular metal composite, anodizing and electrochemical etching of the etching liquid, the problem of difficulty in forming micropores on the surface of the irregular metal composite in the prior art is solved, and efficient micropore formation and plastic parts bonding strength are achieved.

CN119753780APending Publication Date: 2025-04-04FUTAIHUA PRECISION ELECTRONICS (JIYUAN) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411874608.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively form micropores on the local surface of irregularly shaped metal composites, affecting the bonding strength with plastic parts.

Method used

The first metal portion of the metal composite is roughened by an etching liquid, and then anodized to form an oxide film, and a plurality of micropores are formed on the surface of the first metal portion by electrochemical etching.

Benefits of technology

The efficient formation of micropores of the required size on the surface of irregularly shaped metal composites is achieved, and the bonding strength between plastic parts and metal parts is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753780A_ABST
    Figure CN119753780A_ABST
Patent Text Reader

Abstract

A surface treatment method for a metal composite body, comprising: providing a metal composite body, comprising a first metal part and a second metal part integrated into one body; roughening the exposed surface of the first metal part of the metal composite body by using an etching solution; anodizing the roughened metal composite body to form an oxide film on the surface of the second metal part; and etching the anodized first metal part of the metal composite body by electrochemical etching to form a plurality of micropores. The metal composite body is firstly corroded to roughen the surface of the first metal part, and then the metal composite body is anodized to form an aluminum oxide film on the surface of the second metal part of the metal composite body, and then electrochemical etching is performed to etch micropores of a desired size on the surface of the first metal part.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of metal sheet processing, and in particular to a surface treatment method for a metal composite. Background Art

[0002] In the prior art, plastic parts are usually formed on the surface of metal workpieces by injection molding. In order to improve the bonding strength between the plastic part and the metal workpiece, the existing method is to etch the metal workpiece to form micropores, so that during the injection molding process, the molten plastic can enter the micropores of the metal workpiece, thereby effectively improving the bonding strength between the metal and the plastic part. Therefore, it is necessary to etch the metal workpiece with micropores before combining it with the plastic part. Summary of the invention

[0003] In view of this, it is necessary to provide a surface treatment method for a metal composite, which can be applied to the formation of micropores on the local surface of a metal composite with an irregular shape.

[0004] A surface treatment method for a metal composite body, comprising: providing a metal composite body including a first metal portion and a second metal portion integrated into one body; roughening the exposed surface of the first metal portion in the metal composite using an etching solution; and anodizing the roughened metal composite to form an oxide film on the surface of the second metal portion; The first metal portion of the anodized metal composite is etched by electrochemical etching to form a plurality of micropores.

[0005] In one embodiment, the first metal part is made of titanium, titanium alloy or steel, and the second metal part is made of aluminum or aluminum alloy.

[0006] In one embodiment, the etching solution includes 40%-60% by mass of phosphoric acid, 25%-35% by mass of sulfuric acid, 2%-5% by mass of a catalyst, 2%-3% by mass of a corrosion inhibitor, 1%-2% by mass of a surfactant, and the remainder of water; in the etching solution, the total concentration of the phosphoric acid and the sulfuric acid is 500-650 g / L.

[0007] In one embodiment, the catalyst is copper sulfate, the corrosion inhibitor includes molybdate and benzotriazole, and the surfactant is sodium dodecylbenzene sulfonate.

[0008] In one embodiment, the roughening treatment includes: controlling the temperature of the etching solution to 70-80° C., and immersing the metal composite in the etching solution for 3-10 minutes.

[0009] In one embodiment, the surface treatment method further comprises performing a pore sealing treatment on the second metal portion of the metal composite after anodizing and before electrochemical etching.

[0010] In one embodiment, the electrolyte contains 30%-50% by weight of sulfuric acid, 15%-25% by weight of the first solution, and the balance of water; The first solution includes ethylene glycol with a mass percentage concentration of 15%-25%, a corrosion inhibitor with a mass percentage concentration of 3%-5%, a dispersant with a mass percentage concentration of 5%-10%, and the balance of water.

[0011] In one embodiment, the corrosion inhibitor is a benzotriazole cathode corrosion inhibitor, and the dispersant is triethanolamine.

[0012] In one embodiment, the electrochemical etching comprises: The metal composite is used as an anode, an etching electrolyte is used, and the etching electrolyte includes 5%-15% sodium chloride, 3%-15% ferric chloride and the balance water. Direct current is passed with a voltage of 60-100V to etch the surface of the first metal part to form micropores.

[0013] In one embodiment, after the electrochemical etching, a plurality of micropores are formed on the surface of the first metal part, and each of the micropores has a pore diameter of 40-100 μm and a depth of 20-80 μm.

[0014] The present application pre-treats the metal composite, firstly corrodes the metal composite with a chemical etching solution, so that the surface of the first metal part is etched to achieve a roughening effect, then anodizes the metal composite to form an aluminum oxide film on the surface of the second metal part of the metal composite, and then electrochemically etches the pre-treated metal composite to effectively etch micropores of a desired size on the surface of the first metal part. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 A schematic flow chart of a surface treatment method for a metal composite provided in an embodiment of the present application.

[0016] Figure 2 FIG. 1 is a schematic diagram of a metal composite according to an embodiment of the present application.

[0017] Figure 3 A schematic diagram of a sub-process of a surface treatment method of a metal composite provided in an embodiment of the present application.

[0018] Figure 4 It is an enlarged schematic diagram of the metal titanium portion of the embodiment before the roughening treatment.

[0019] Figure 5 This is an enlarged schematic diagram of the metal titanium part after roughening treatment.

[0020] Description of main component symbols: The metal composite 10 , the first metal portion 11 , and the second metal portion 12 . DETAILED DESCRIPTION

[0021] In order to more clearly understand the purpose, features and advantages of the present application, the present application is described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that, in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other. In the following description, many specific details are set forth to facilitate a full understanding of the present application, and the embodiments described are only a part of the embodiments of the present application, rather than all of the embodiments.

[0022] The present application provides a surface treatment method for a metal composite. The metal composite includes a first metal part and a second metal part, the material of the second metal part is aluminum or an aluminum alloy, and the material of the first metal part is titanium, a titanium alloy or steel. The first metal part and the second metal part are not in a uniformly mixed state, and the first metal part and the second metal part have a bonding interface. The first metal part and the second metal part of the metal composite can be combined into one by forging, cold / hot rolling, explosive forming, welding, etc.

[0023] The surface treatment method of the metal composite of the present application aims to form micropores on the surface of the first metal part of the metal composite by etching, while the surface of the second metal part does not form micropores, so that a plastic part can be subsequently formed by injection molding on the surface of the first metal part. During the injection molding process, the molten plastic can enter the micropores of the first metal part, thereby effectively improving the bonding strength between the plastic part and the first metal part. The surface treatment method of the metal composite of the present application can be applied to the formation of micropores in metal composites of irregular shapes.

[0024] See also Figure 1 , Figure 1 A schematic diagram of a surface treatment method for a metal composite provided in an embodiment of the present application is shown in FIG. Figure 1 As shown, the method for trimming the metal composite provided in the above embodiment of the present application includes the following steps S1 to S3: In step S1, Figure 2 As shown, a metal composite body 10 of an embodiment includes a first metal part 11 and a second metal part 12 that are integrated into one body, and the first metal part 11 and the second metal part 12 have a bonding interface. The material of the second metal part 12 is aluminum or an aluminum alloy, and the material of the first metal part 11 is titanium, a titanium alloy or steel. The outer surface of the metal composite body 10 includes the surface of the first metal part 11 and the surface of the second metal part 12. Figure 2 The above is only one way of combining the first metal part 11 and the second metal part 12, and is not limited to Figure 2 In summary, the first metal portion 11 and the second metal portion 12 can be combined in other ways, such as a stacking combination or other irregular combination methods.

[0025] The purpose of the pretreatment in step S2 is to form micropores on the surface of the first metal part of the metal composite in the subsequent step S3 without forming micropores on the surface of the second metal part.

[0026] like Figure 3 As shown, step S2 further includes steps S201 and S202.

[0027] Step S201: using an etching solution to roughen the exposed surface of the first metal part in the metal composite.

[0028] Step S201 uses a chemical wet etching method to immerse the metal composite in an etching solution for etching. The etching solution selectively etches the surface of the first metal part, while rarely or substantially not etching the surface of the second metal part.

[0029] After step S201, the surface of the first metal part is roughened to form an uneven state. Since the subsequent step S3 requires electrochemical etching of the first metal part, if the surface of the first metal part is smooth, it is not conducive to electrochemical etching, resulting in that the electrochemical etching of step S3 cannot be effectively performed, and thus the desired micropores cannot be obtained. Therefore, by pre-treating the metal composite, the surface of the first metal part is made uneven, and the uneven surface forms a tip discharge during the electrochemical etching process, which is more conducive to etching the first metal part, and thus forming the desired micropores.

[0030] In the embodiment of the present application, the etching solution is an aqueous solution mainly containing phosphoric acid and sulfuric acid. The etching solution includes phosphoric acid with a mass percentage concentration of 40%-60%, sulfuric acid with a mass percentage concentration of 25%-35%, a catalyst with a mass percentage concentration of 2%-5%, a corrosion inhibitor with a mass percentage concentration of 2%-3%, a surfactant with a mass percentage concentration of 1%-2%, and the remainder of water. In some embodiments, in the etching solution, the total concentration of phosphoric acid and sulfuric acid is 500-650g / L. The etching solution can effectively achieve that the etching solution selectively etches the surface of the first metal part, while etching less or substantially not etching the surface of the second metal part.

[0031] In one embodiment, the etching solution includes 50% by mass phosphoric acid, 30% by mass sulfuric acid, and 3% by mass catalyst.

[0032] The catalyst in the etching solution is copper sulfate. The copper ions in copper sulfate have certain catalytic activity. In the chemical roughening process involving redox reaction, they act as catalysts to accelerate the reaction rate, improve the roughening efficiency, and enable the workpiece surface to reach the required roughness and cleanliness more quickly.

[0033] In the etching solution, the corrosion inhibitor includes molybdate and benzotriazole. In the present application, there is no specific requirement for the ratio of molybdate and benzotriazole. The compounding of molybdate and benzotriazole can produce a synergistic effect and has a good corrosion inhibition effect. On the one hand, molybdate mainly forms an oxide film on the metal surface to inhibit corrosion, while benzotriazole exerts a corrosion inhibition effect by adsorbing and forming a film on the metal surface. The film-forming mechanisms of the two complement each other, and after compounding, they can provide protection on a wider range of metal material surfaces. On the other hand, in a complex corrosive environment, a single corrosion inhibitor may fail due to environmental factors (such as temperature changes, changes in medium composition, etc.), and the compounded corrosion inhibitor can enhance the ability to resist environmental changes. For example, in an aqueous solution containing a variety of corrosive ions, a compounded corrosion inhibitor can simultaneously cope with the corrosive effects of different ions, making the corrosion inhibition efficiency higher than when used alone.

[0034] In the embodiment of the present application, the surfactant is sodium dodecylbenzene sulfonate, which is an anionic surfactant that reduces the surface tension of the etching solution and improves the wetting effect of the etching solution on the metal composite.

[0035] The roughening treatment includes: controlling the temperature of the etching solution to 70-80° C., immersing the metal composite in the etching solution for 3-10 minutes. In one embodiment, the temperature of the etching solution is controlled to 75° C., and the metal composite is immersed in the etching solution for 7 minutes.

[0036] The use of chemical etching liquid to roughen the metal composite is sensitive to the reaction temperature (temperature of the etching liquid) and the concentration of the reagent (concentration of each component of the etching liquid). Therefore, it is necessary to accurately control the temperature of the etching liquid and the concentration of each component of the etching liquid, and to obtain the desired roughening effect by controlling the roughening treatment time.

[0037] After the roughening treatment, the surface roughness of the first metal part of the metal composite reaches 4-6 μm. The first metal part with such roughness is more conducive to the subsequent electrochemical etching of the first metal part to form micropores.

[0038] The metal composite is roughened by using a chemical etching solution, which is not limited by the surface morphology of the metal composite, for example, depressions, corners, holes, etc. can all be effectively roughened. The roughening treatment makes the surface of the first metal part uneven, which is conducive to the subsequent electrochemical etching of the first metal part.

[0039] Figure 4This is an enlarged schematic diagram of the titanium metal portion of the metal composite of the embodiment before the roughening treatment (magnification 200), Figure 5 This is an enlarged schematic diagram of the metal titanium part after roughening (magnification 200). Figure 4 and Figure 5 By comparison, it can be seen that after roughening, obvious point-shaped corrosion pits are formed on the surface of the metal titanium part.

[0040] Step S202, anodizing the roughened metal composite, wherein the anodizing process oxidizes the surface of the second metal portion to form an oxide film and avoids or reduces oxidation of the first metal portion.

[0041] If the surface of the first metal part is oxidized more during the anodizing process, resulting in the formation of a thicker oxide film, that is, the metal M oxide film covers the surface of the first metal part, the electrochemical etching in step S3 will not be able to effectively etch the first metal part, and thus the desired micropores cannot be etched. Therefore, in the present application, the oxidation of the first metal part needs to be minimized or avoided during the anodizing process. In the embodiment of the present application, the electrolyte used in the anodizing process contains ethylene glycol, which, as a corrosion inhibitor, can effectively inhibit the oxidation of the first metal part in the metal composite, thereby avoiding or reducing the oxidation of the first metal part.

[0042] Anodizing is an electrochemical oxidation process that uses an applied current under specific electrolyte and process conditions to form an oxide film on the surface of aluminum / aluminum alloy. This process can not only improve the corrosion resistance, wear resistance and decorative properties of aluminum / aluminum alloy, but also overcome the defects of low surface hardness and poor wear resistance of aluminum / aluminum alloy, thereby extending its service life and expanding its application range. Anodizing is widely used and is often used for surface treatment of various aluminum products, such as automotive parts, building decoration materials, electronic product housings, etc.

[0043] In the present application, during anodization, the metal composite is used as an anode and placed in an electrolyte to undergo an oxidation reaction with hydrogen ions in the electrolyte to generate aluminum oxide and water (an oxide film is formed on the surface of the second metal part), while releasing electrons; in the cathode reaction, water is reduced to hydrogen. As the reaction proceeds, a layer of aluminum oxide film gradually forms on the aluminum surface, and the thickness of the aluminum oxide film can be adjusted as needed.

[0044] It is understandable that the metal composite can be subjected to some pre-treatments before anodizing, such as cleaning, pickling, alkaline etching, etc. The surface of the metal composite needs to be cleaned to remove oil and impurities to ensure a clean surface to ensure the quality of the anodizing effect. The metal composite will be soaked in an acidic solution for pickling to remove the oxide scale and oxide on the surface and improve the anodizing effect. Alkaline etching removes the natural oxide film and slight scratches on the surface.

[0045] In the present application, the electrolyte is prepared by using sulfuric acid, a first solution containing ethylene glycol, and water. In the embodiment of the present application, the electrolyte contains 30%-50% sulfuric acid by mass, 15%-25% of the first solution by mass, and the balance of water. Among them, the first solution includes 15%-25% ethylene glycol by mass, 3%-5% corrosion inhibitor by mass, 5%-10% dispersant by mass, and the balance of water. The first solution can effectively improve the toughness, corrosion resistance, and life of the aluminum oxide film, inhibit the growth of titanium oxide film, and reduce the film thickness of titanium oxide film.

[0046] In the embodiment of the present application, the corrosion inhibitor is a benzotriazole cathode corrosion inhibitor, and the dispersant is triethanolamine.

[0047] In some embodiments, during the anodizing treatment, the temperature of the electrolyte is controlled at 3-7°C, the voltage is 28-32V, and the treatment time is 60-70 minutes. Typically, an oxide film with a thickness of about ten microns is formed.

[0048] By using an electrolyte prepared with sulfuric acid, a first solution containing ethylene glycol, and water, a uniform oxide film can be controlled to be formed on the surface of the second metal part of the metal composite. The first solution can effectively improve the toughness, corrosion resistance, and life of the aluminum oxide film layer, and inhibit the growth of the titanium oxide film and reduce the film thickness of the titanium oxide film.

[0049] In some embodiments, after the anodizing treatment, the metal composite is further subjected to a pore sealing treatment. The pore sealing treatment is to perform a pore sealing treatment on the surface of the anodized second metal part to seal the micropores of the oxide film to improve its corrosion resistance and sealing performance. The pore sealing treatment can be performed using a nickel-containing pore sealing agent solution.

[0050] In some embodiments, in the sealing treatment, the sealing agent solution adopts an aqueous solution of nickel acetate with a concentration of 8-12 g / L, the temperature of the sealing agent solution is controlled at 85-95°C, the power supply voltage is 60-100V, and the treatment time is 50-60min.

[0051] The step S3 is to etch the first metal portion of the pre-treated metal composite to form a plurality of micropores.

[0052] Electrochemical etching is a technology that uses electrochemical reactions to perform precise processing on metal surfaces. The basic principle is that the metal acts as the anode. During the electrolysis process, the specific area of ​​the metal surface will be corroded by the action of electric current to form the desired pattern or shape.

[0053] The present application configures a specific etching electrolyte. In the present application, the etching electrolyte includes 5%-15% sodium chloride and 3%-15% ferric chloride and the balance of water. The etching electrolyte can react with the first metal part of the metal composite without corroding the aluminum oxide film formed during the anodizing process.

[0054] Electrochemical etching uses a metal composite as the anode and a graphite rod or stainless steel as the cathode. The two are immersed in an etching electrolyte, that is, the two are connected by the etching electrolyte. Direct current is passed through, and under the action of the current, the first metal part on the anode loses electrons, forming metal ions that enter the electrolyte, thereby forming corrosion on the metal surface. By controlling parameters such as current, voltage, and electrolyte composition, the depth and shape of etching can be precisely controlled.

[0055] In some embodiments, during the electrochemical etching process, the temperature of the etching electrolyte is controlled to be 45-65°C, the power-on voltage is 60-100V, and the power-on time is 5-15min. By setting the above electrochemical etching process parameters, the first metal portion is etched to obtain micropores of the desired pore size and depth. In one embodiment, the temperature of the etching electrolyte is controlled to be 55°C, the power-on voltage is 90V, and the power-on time is 10min.

[0056] In addition, in some embodiments, when the metal composite needs to be corroded to form micropores on a local surface of the first metal part, a conductive jig can be used to cover the metal composite to mask a part of the first metal part of the metal composite, so that micropores are formed in the unmasked area of ​​the first metal part of the metal composite.

[0057] After electrochemical etching, a plurality of micropores are formed on the surface of the metal M of the metal composite, each micropore having a pore size of 40-100 μm and a depth of 20-80 μm. The micropores of the above pore size and depth can allow the molten plastic to enter the micropores during the subsequent injection molding process.

[0058] The electrochemically etched metal composite can provide high-quality materials for subsequent deep processing of the product, thereby improving production efficiency. For example, a plastic part can be formed on the metal composite by injection molding. During the injection molding process, the molten plastic enters the micropores of the first metal part, so that the plastic part is firmly combined with the metal composite.

[0059] The present application pre-treats the metal composite, firstly uses a chemical etching solution of a specific formula to corrode the metal composite, so that the surface of the first metal part is etched to achieve a roughening effect, which can promote the subsequent electrochemical etching of the first metal part, and then uses an electrolyte of a specific formula to anodize the metal composite, so that an oxide film is formed on the surface of the second metal part of the metal composite, so that the oxide film can serve as a protective barrier layer of the second metal part in the subsequent electrochemical etching process, and then the pre-treated metal composite is electrochemically etched, and an etching electrolyte of a specific formula is used to effectively etch micropores of a desired size on the surface of the first metal part.

[0060] It is obvious to those skilled in the art that the present application is not limited to the details of the exemplary embodiments described above, and that the present application can be implemented in other specific forms without departing from the spirit or essential features of the present application. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present application is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present application.

[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the preferred embodiments, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.

Claims

1. A method for surface treatment of a metal composite, characterized in that: include: providing a metal composite body including a first metal portion and a second metal portion integrated into one body; roughening the exposed surface of the first metal portion of the metal composite using an etching solution; as well as anodizing the roughened metal composite to form an oxide film on the surface of the second metal portion; The first metal portion of the anodized metal composite is etched by electrochemical etching to form a plurality of micropores.

2. The surface treatment method of a metal composite according to claim 1, characterized in that: The first metal part is made of titanium, titanium alloy or steel, and the second metal part is made of aluminum or aluminum alloy.

3. The surface treatment method of a metal composite according to claim 2, characterized in that: The etching solution comprises 40%-60% by mass of phosphoric acid, 25%-35% by mass of sulfuric acid, 2%-5% by mass of a catalyst, 2%-3% by mass of a corrosion inhibitor, 1%-2% by mass of a surfactant, and the remainder of water; in the etching solution, the total concentration of the phosphoric acid and the sulfuric acid is 500-650 g / L.

4. The surface treatment method of a metal composite according to claim 3, characterized in that: The catalyst is copper sulfate, the corrosion inhibitor includes molybdate and benzotriazole, and the surfactant is sodium dodecylbenzene sulfonate.

5. The surface treatment method of a metal composite according to any one of claims 2 to 3, characterized in that: The roughening treatment includes: controlling the temperature of the etching solution to 70-80° C., immersing the metal composite in the etching solution for 3-10 minutes.

6. The surface treatment method of a metal composite according to claim 1, characterized in that: The surface treatment method further includes performing a pore sealing treatment on the second metal portion of the metal composite after anodizing and before electrochemical etching.

7. The surface treatment method of a metal composite according to claim 6, characterized in that: The electrolyte used in the anodization contains 30%-50% by weight of sulfuric acid, 15%-25% by weight of the first solution, and the balance of water; The first solution includes ethylene glycol with a mass percentage concentration of 15%-25%, a corrosion inhibitor with a mass percentage concentration of 3%-5%, a dispersant with a mass percentage concentration of 5%-10%, and the balance of water.

8. The surface treatment method of a metal composite according to claim 7, characterized in that: The corrosion inhibitor is a benzotriazole cathode corrosion inhibitor, and the dispersant is triethanolamine.

9. The surface treatment method of a metal composite according to claim 1, characterized in that: The electrochemical etching comprises: The metal composite is used as an anode, an etching electrolyte is used, and the etching electrolyte includes 5%-15% sodium chloride, 3%-15% ferric chloride and the balance water. Direct current is passed with a voltage of 60-100V to etch the surface of the first metal part to form micropores.

10. The surface treatment method of a metal composite according to claim 1, characterized in that: After the electrochemical etching, a plurality of micropores are formed on the surface of the first metal part, each of the micropores has a pore diameter of 40-100 μm and a depth of 20-80 μm.

Citation Information

Cited By

  • Environment-friendly method for electroplating and activating surface of superfine refractory metal wire

    CN120425428A